Characterization of Mating Type Genes in Aspergillus flavus Populations from Two Locations in Kenya - Ouko Abigael; Okoth Sheila; Amugune Nelson; Vesa Joutsjoki (Advances in Agriculture)
In this study, the possibility of sexual reproduction in sampled Aspergillus flavus strains was evaluated by assessing the distribution of mating type (MAT) genes, which are known to control sexual character among fungi, for two counties in Kenya. Forty-four isolates from Nandi and Makueni counties were genotyped by MAT using a multiplex polymerase chain reaction assay. The primer pair for the MAT1-1 amplified a 396 base pair (bp) fragment containing an α-box motif, and MAT1-2 primers targeted a 270 bp segment with a high mobility group protein. The MAT1-2 genes dominated in both regions although the frequency was higher in Nandi (75%) than in Makueni (54.17%). There were no MAT1-1 genes sampled in Nandi, and in Makueni their proportion was 15.91%. The percentage of isolates that amplified for both MAT genes in Makueni was 9.09%, while in Nandi it was 11.36%. Currently, use of aggressive aflatoxin non-producing A. flavus strains as biocontrol is the most promising preharvest aflatoxin control strategy in Kenya. However, we address the possibility of introduced biocontrol strains to breed with existing aflatoxin producing strains in nature, which could lead to the generation of A. flavus offspring capable of aflatoxin production while also being aggressive colonizers and possibly increasing the burden of aflatoxin exposure in food.